Dinamika Kepercayaan Konsumen Terhadap Visualisasi Iklan Berbasis AI di Marketplace - Nurmono; Syamsul Mu`arif; Yulianto; Bagus Saputra (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the impact of artificial intelligence (AI) utilization in product advertising visualization on consumer trust and responses within e-commerce platforms, particularly Shopee. Along with the increasing adoption of AI in generating more aesthetic and appealing visual content, concerns have emerged regarding the discrepancy between product representations in advertisements and the actual conditions of products received by consumers. This research employs a mixed-method approach, combining qualitative analysis of consumer reviews and visual product observations with quantitative analysis through the measurement of consumer response frequencies. The data were collected from ten popular products on Shopee that utilize AI-based visual content. The findings indicate that the use of AI in advertising is correlated with increased consumer distrust, as reflected in complaints about product discrepancies, perceptions of exaggerated advertising, and a growing demand for authentic evidence such as real-time photos or videos. Nevertheless, some consumers still exhibit positive responses toward the visual appeal generated by AI. These results suggest that AI plays a dual role as both an enhancer of visual aesthetics and a potential factor that may undermine credibility. Therefore, more transparent and ethical marketing strategies in the use of AI are required to maintain consumer trust. This study contributes to a deeper understanding of the dynamic relationship between AI technology, visual communication, and consumer behavior in the context of e-commerce.